Outcomes of treatment with cyclic administration of dienogest after ovarian endometriotic cystectomy. (3rd August 2015) - Yanase, Toru; Ishida, Manako; Nishijima, Shota; Morikawa, Kyoko; Yokoo, Tomokazu; Takaki, Yoshihiro; Tsuneki, Ikunosuke; Tamura, Masaki; Kurabayashi, Takumi
Abstract: To evaluate the outcomes of patients treated with cyclic administration of dienogest after ovarian endometriotic cystectomy, following the completion of treatment. We retrospectively evaluated 26 patients treated with dienogest (2 mg/day) after cystectomy (revised American Society for Reproductive Medicine [r-ASRM] stage III–IV) in a pilot study. Dienogest was administered cyclically, for a total of six cycles, each comprising three weeks on and one week off. Outcomes of interest included severity of menstrual pain and recurrence of cysts at baseline, during the immediate post-treatment period and at the final outpatient follow-up. The mean outpatient follow-up period was 45.0 months. The visual analog scale score for menstrual pain following 6 cycles of dienogest treatment was significantly lower than that at baseline; it remained low at the final follow-up. The recurrence rates of cysts were 4% and 21% at 24 and 48 months after the completion of dienogest treatment, respectively. Six patients with recurrent disease were all classified as having r-ASRM stage IV. Our results suggest that cyclic dienogest for six months after cystectomy could relieve menstrual pain and reduce the recurrence of cysts, for approximately four years. The necessary treatment period for patients with r-ASRM stage IV disease requires further study. Chinese abstract: 研究的目的为评估地诺孕素周期性治疗对卵巢子宫内膜异位囊肿切除术后患者的治疗效果。我们回顾性地分析了一项试验研究中26位内异囊肿切除术（修订版美国生殖医学会[r-ASRM] Ⅲ-Ⅳ期）后服用地诺孕素（2mg/天）的患者。地诺孕素行周期式给药方式，共6个周期，每周期服药3周停药1周。研究观察基线期、治疗结束后以及末次随访时患者的痛经程度和囊肿复发情况。平均随访期为45个月。6个周期治疗结束时患者的痛经视觉模拟评分显著低于基线期；末次随访时仍保持较低水平。异位囊肿的复发率在地诺孕素治疗结束后的24个月与48个月分别为4%和21%。研究中6位复发的患者均为r-ASRM Ⅳ期。研究结果提示，在囊肿切除术后行6个月的地诺孕素周期性治疗可以有效改善痛经症状，降低囊肿的复发率，且效果可能维持4年。在将来的研究中还需要进一步研究r-ASRM Ⅳ期患者的治疗情况。